2022
DOI: 10.1155/2022/8487737
|View full text |Cite
|
Sign up to set email alerts
|

Cushing Syndrome in a Pediatric Patient with Topical Steroid Overuse

Abstract: Cushing syndrome is a state of hypercortisolism from exogenous or endogenous exposure to glucocorticoids resulting in various clinical manifestations. In this case report, we present a case of a 15-month-old child who presented with cushingoid facies due to over-the-counter misuse of a very potent topical steroid (clobetasol 0.05%) for suspected scabies. Laboratory measurement of urinary free cortisol level was low, and 8 : 00 am basal cortisol level was measured, which was decreased, which confirmed the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Though rare, Cushing's syndrome (CS) has been reported in children. [1][2][3][4][5][6][7][8][9][10][11][12][13] Aitafo et al reported Cushing's syndrome as being responsible for <1% of all cases presenting in the Paediatric Endocrinology clinic in South-south Nigeria. 12 This is similar to that reported by Tamunopriye et al where CS was responsible for 0.5% of all cases seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though rare, Cushing's syndrome (CS) has been reported in children. [1][2][3][4][5][6][7][8][9][10][11][12][13] Aitafo et al reported Cushing's syndrome as being responsible for <1% of all cases presenting in the Paediatric Endocrinology clinic in South-south Nigeria. 12 This is similar to that reported by Tamunopriye et al where CS was responsible for 0.5% of all cases seen.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with common manifestations of Cushing's syndrome reported-obesity, moon face, hirsutism, muscle weakness, hypertension and glucose intolerance. 13,15 Hypertension is seen in up to 80% of patients with CS and correlates with the duration of hypercortisolism. 16 Azzoug et al reported hypertension in 67% of patients with CS, 33% of whom had glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation